Anxiety and depression, cognitive coping strategies, and health locus of control in patients with digestive system cancer - Kulpa, Marta; Kosowicz, Mariola; Stypuła-Ciuba, Beata J.; Kazalska, Dorota (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction : Contemporary psycho-oncology focuses on the study of the psychological determinants of the functioning of cancer patients. Among the psychological factors that significantly affect the functioning of the patients are anxiety and depressive disorders. Aim: To assess the psychological functioning of patients with digestive system cancer in the cancer-treating process and to develop guidelines for psychological care dedicated to this group of patients based on the results of the study. Material and methods : A total of 69 patients aged 23 to 91 (average 56) years with digestive system cancer treated in the Gastroenterology Cancer Clinic in the Institute of Oncology in Warsaw were examined using HADS, Mini-MAC, and MHLC. The results were analysed using statistical tests and correlation analysis. Another 532 patients from other wards formed the reference group. Results: Measured HLC, anxiety, and depression did not differ significantly from the overall patient population. The investigation of the relationships between anxiety and depression and mental adjustment to cancer showed a positive correlation between anxiety and depression and anxious preoccupation and hopelessness-helplessness, and negative correlation between anxiety and depression and fighting spirit. Conclusions : The obtained research results on the correlation of anxiety and depression with health locus of control show that the lower the severity of anxiety and depression, the higher the severity of internal health locus of control. The results confirm the necessity of psychological support forcancer patients showing evidence of destructive attitudes and external health locus of control, so that the severity of anxiety-depressive disorders can indirectly be reduced.